2022
DOI: 10.3390/ani12091127
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Genomic and Functional Association Study for Workability and Calving Traits in Holstein Cattle

Abstract: The goal of our study was to identify the SNPs, metabolic pathways (KEGG), and gene ontology (GO) terms significantly associated with calving and workability traits in dairy cattle. We analysed direct (DCE) and maternal (MCE) calving ease, direct (DSB) and maternal (MSB) stillbirth, milking speed (MSP), and temperament (TEM) based on a Holstein-Friesian dairy cattle population consisting of 35,203 individuals. The number of animals, depending on the trait, ranged from 22,301 bulls for TEM to 30,603 for DCE. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Modulation of synaptic transmission, a significantly enriched BP for FY candidate genes, plays a crucial role in neuronal signaling and information processing in the nervous system ( https://www.ebi.ac.uk/QuickGO/term/GO:0050804 ). Modulation of synaptic transmission was associated with maternal calving ease in Holstein cows [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Modulation of synaptic transmission, a significantly enriched BP for FY candidate genes, plays a crucial role in neuronal signaling and information processing in the nervous system ( https://www.ebi.ac.uk/QuickGO/term/GO:0050804 ). Modulation of synaptic transmission was associated with maternal calving ease in Holstein cows [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the gene associated with the most traits in the novel subject test (SESTD1) was highly expressed in domestic cattle brains. Additionally, it was shown that at least seven SNPs connected with temperament determined in the studies by Jakimowicz et al [ 58 ] were localized on the X chromosome. Moreover, in Brahman cattle, genomic regions and genes related to temperament have recently been identified [ 59 ].…”
Section: Temperament—the Impact Of Individual Characteristics Living ...mentioning
confidence: 99%
“…Estimated pedigree-based heritabilities for milking temperament ranged from 0.04-0.47 in dairy cattle milked in conventional milking systems [3,135]. For milking speed or milk flow, heritabilities ranged from 0.12 to 0.44 [136][137][138] when calculated using pedigrees or a genomic relationship matrix. Ebinghaus et al [9,76] evaluated the suitability of different behaviour tests describing cow-human relationships for breeding (e.g., avoidance or distance toward an unfamiliar person, tolerance to tactile interaction).…”
Section: Behaviour Response To Human Handlingmentioning
confidence: 99%
“…Chen et al [167] detected 40 and 35 significantly associated SNPs with milking temperament and milking speed respectively in a population of ~4000 North American HF dairy cows (Table S1). Jakimowicz et al [136] associated seven SNPs located on chromosome X (explaining 1.9% of the phenotypic variance) with milking temperament, and 24 SNPs with milking speed (explaining 5.8% of the phenotypic variance) (Table S1).…”
Section: Behaviour Response To Human Handlingmentioning
confidence: 99%